The Contribution of an Ionic Peroxidase Isozyme to Enzyme-Mediated Browning in Dioscorea esculenta L. Tubers - Omidiji, O.; Okpuzor, J.E.; Otubu, O. (Pakistan Journal of Nutrition, 2006)
The time course of the activity of a strongly ionic peroxidase (POD) isozyme from Dioscorea esculenta Var. fasiculata tissues correlated with that of tissue browning during incubation at room temperature for 24 hours. Tissue browning was inhibited by 1 mM DTT (a peroxidase-specific inhibitor) by 40%; by about 75 % by 1 mM PVP (a polyphenol oxidase-specific inhibitor) and completely by a combination of DTT and PVP at 1 mM. Moreover, a temperature profile study revealed that POD activity was high at temperatures (up to 60 o C) during enhanced browning but not limited to it. This strongly ionic POD isozyme contributes up to 40% of enzyme-related tissue browning in Diocorea esculenta especially at temperature above 40 o C. This is based on results derived from inhibition by PVP. The results support our view that high temperature enzyme-mediated browning in this tissue is more of a POD activity which should be considered in the overall processing of yam tissues